Increased Risk of Short-Term Complications in Smokers Undergoing Primary Unicompartmental Knee Arthroplasty - Carender, Christopher N.; DeMik, David E.; Bedard, Nicholas A.; Glass, Natalie A.; Brown, Timothy S. (The Journal of Knee Surgery, 2020)
The effects of smoking on unicompartmental knee arthroplasty (UKA) are unknown. The purpose of this study was to evaluate the effects of smoking on short-term outcomes following primary UKA. A query of the National Surgical Quality Improvement Project (NSQIP) database was used to identify cases of primary UKA performed during years 2006 to 2017. Patient demographics, operative times, and postoperative complications were compared between smoking and nonsmoking cohorts. Descriptive statistics, univariate analyses, and multivariate analyses were conducted to evaluate the effects of smoking on primary UKA. A total of 10,593 cases of UKA were identified; 1,046 of these patients were smokers. Univariate analysis demonstrated smokers to have higher rates of any complication (4.6 vs. 3.3%, p = 0.031), any wound complication (1.82 vs. 0.94%, p = 0.008), deep wound infection (0.57 vs. 0.13%, p = 0.006), and reoperation (1.34 vs. 0.68%, p = 0.018) relative to nonsmokers. Multivariate analysis demonstrated smokers to have higher rates of any wound complication (odds ratio [OR] = 1.79; 95% confidence interval [CI]: 1.06–2.95) and reoperation (OR = 2.11; 95% CI: 1.12–3.97). Smokers undergoing primary UKA are at higher risk for any wound complication and reoperation relative to nonsmokers in the first 30 days postoperatively. Further studies evaluating the long-term effects of smoking on outcome following UKA, as well as the impact of smoking cessation on outcomes following UKA, are needed.
Keywords: unicompartmental knee arthroplasty; smoking; complication; wound; infection; NSQIP